2020
DOI: 10.1002/dc.24660
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of urine cytology in detecting histologic variants of urothelial carcinomas in the urinary bladder: Cytopathologic correlation of 72 cases

Abstract: Background Precise identification of histologic variants in urothelial carcinoma (UC) is important because some histologic types have a poor prognosis and clinical management varies. Urine cytology is used for bladder cancer screening, but the cytomorphologic features of histologic variants have not been well described. In the current study, we evaluate the effectiveness of urine cytology in detecting histologic variants of UC in the urinary bladder. Methods Seventy‐two urine cytology specimens from patients d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…44,45 In UTC, there are only a few reports of cases described as showing micropapillary features. [46][47][48][49] However, these features are very subtle in urine specimens, most notably lacking the easiest-to-recognize feature, which is the presence of lacunar retraction seen in tissue samples. In UTC, tumour cells are typically in small three-dimensional clusters with no fibrovascular cores and with regular borders, showing minimal scalloping at the edges (Figure 4).…”
Section: Micropapillary Urothelial Carcinomamentioning
confidence: 99%
See 2 more Smart Citations
“…44,45 In UTC, there are only a few reports of cases described as showing micropapillary features. [46][47][48][49] However, these features are very subtle in urine specimens, most notably lacking the easiest-to-recognize feature, which is the presence of lacunar retraction seen in tissue samples. In UTC, tumour cells are typically in small three-dimensional clusters with no fibrovascular cores and with regular borders, showing minimal scalloping at the edges (Figure 4).…”
Section: Micropapillary Urothelial Carcinomamentioning
confidence: 99%
“…These studies describe large, discohesive cells with abundant dense and variably vacuolated cytoplasm and eccentrically placed large, round, and hyperchromatic nuclei with coarse chromatin and inconspicuous nucleoli (Figure 5). 46,47,49,62,63 Furthermore, a large study was performed reviewing UTC specimens in patients diagnosed with urothelial CIS with plasmacytoid features on biopsy. 64 In this study, similar cytomorphologic changes were seen in UTC as the invasive variant; however, most cases did not meet TPS criteria, largely because abundant cytoplasm, resulting in a low N:C ratio, is a characteristic feature of this variant.…”
Section: Plasmacytoid Urothelial Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…In a report of urine cytology cases involved by UCSD, Yoo et al 11 reported that 85% (11 of 13) showed malignant cells with hyperchromatic and markedly atypical nuclei, high nuclear to cytoplasmic (N:C) ratios, and keratinization (dense orangeophilic cytoplasm) (Figs. 1A, B), which matched features of malignant squamous cells in urine cytology from UCSD and PBSQC reported by Owens et al 12 Yoo et al 11 noted that in contrast to CUC cases with abnormal squamous cells mimicking malignant squamous components, morphologic findings of severe squamous nuclear atypia and necrotic debris were present only in patients with carcinomas displaying true squamous differentiation. While features of dyskeratosis and keratinization can be helpful in well-to-moderately differentiated keratinizing malignant squamous components, nonkeratinizing squamous cell carcinomas (SQCs) may display nonspecific malignant features such as hyperchromatic, irregular nuclei in cells with high N:C ratios dispersed as single cells and crowded cell clusters in the background of granular debris and inflammation (Figs.…”
Section: Epithelial Tumors Squamous Cell Carcinomamentioning
confidence: 99%
“…The morphologic features of malignant squamous cells in urine cytology are variable, depending on the degree of differentiation of the tumor and whether it is keratinizing. In a report of urine cytology cases involved by UCSD, Yoo et al 11 reported that 85% (11 of 13) showed malignant cells with hyperchromatic and markedly atypical nuclei, high nuclear to cytoplasmic (N:C) ratios, and keratinization (dense orangeophilic cytoplasm) (Figs. 1A, B), which matched features of malignant squamous cells in urine cytology from UCSD and PBSQC reported by Owens et al 12 Yoo et al 11 noted that in contrast to CUC cases with abnormal squamous cells mimicking malignant squamous components, morphologic findings of severe squamous nuclear atypia and necrotic debris were present only in patients with carcinomas displaying true squamous differentiation.…”
Section: Epithelial Tumors Squamous Cell Carcinomamentioning
confidence: 99%